PREVALENSI DAN KARAKTERISTIK NYERI NEUROPATIK DI INSTALASI RAWAT JALAN NEUROLOGI RSDR HASAN SADIKIN BANDUNG - Danny Bagus Agfiandi*, Henny Anggraini Sadeli*, Yustiani Dikot*,/i. (Neurona Majalah Kedokteran Neuro Sains, 2015)
INTRODUCTION NEUROPATHIC PAIN WILL AFFECT PATIENTS QUALITY OF LIFE DUE TO ITS CHRONICITY AND INTENSITY THE EPIDEMIOLOGIC STUDY OF NEUROPATHIC PAIN IN INDONESIA IS STILL LIMITED THE PATHOMECHANISM OF PAIN CAN BE DETERMINED FROM THE CLINICAL MANIFESTATIONS ACTING AS THE BASIS OF RATIONAL PAIN MANAGEMENT